The effectiveness of thromboprophylaxis after the total hip replacement - Wójcik, Beata; Gębala, Edyta; Drelich-Zbroja, Anna; Jabłoński, Mirosław (Polish Journal of Public Health, 2012)
Introduction. The hip joint often undergoes degenerative changes that significantly reduce its activity and the overall fitness of a patient. Currently, the most common treatment for advanced osteoarthritis of the hip joint is replacement surgery. Unfortunately, the treatment and perioperative period cause the development of venous thrombosis.In Poland about 80-100 thousand people a year are diagnosed with venous thromboembolic disease, one third in the form of pulmonary embolism, and two thirds of “pure” venous thrombosis. The use of efective prevention of this serious compliction depends on the knowledge of clinical risk factors identified during an interview with each patient individually.Aim. The aim of this study was to evaluate the efficiency of blood flow in patients undergoing lower limb systematic antithrombotic exercises and standard course of the therapeutic improvement after the hip replacement.Material and methods. Evaluation of the functional status of veins in 36 women and 24 men was based on ultrasound examination and measurement of the circumference of the leg at the ankle and shin.Results. As a result of statistical analysis it was found that after the surgery, the maximum systolic velocity improved significantly and also the minimum velocity significantly improved statistically.Conclusions. Studies showed a beneficial effect of an early introduction of anticoagulant exercises and physiotherapeutic treatment on blood flow in the veins of the lower limbs.